Nine minutes on Monday : the quick and easy way to go from manager to leader - Robbins, James (McGraw Hill-Ascent Audio, 2012)
The Globe & amp; Mail's #1 Business Book of the Year! "ALL IN, ALL THE TIME" Low performance and high turnover is not the result of lazy, apathetic workers. It's not about decreasing budgets. And it's not about a terrible economy. It's about leadership that doesn't engage employees. In Nine Minutes on Monday, leadership guru James Robbins argues that employee engagement comes down to one thing: a constant dedication to meeting the universal needs that drive performance excellence. In today's chaotic, high-stakes business environment, it is easy to get distracted from leadership responsibilities by focusing on tasks at hand instead of on strategy. But when you neglect to keep your leadership priorities in front of you, everyone suffers--your staff, your organization and, in the end, you. Whether you lead a small team or an entire organization, you'll discover the nine keys to raising productivity, boosting morale, and increasing employee engagement. Nine Minutes on Monday combines proven engagement drivers and principles of human motivation into a simple system of execution that will show immediate results. Inside you'll find: The "9 Minute" template for maintaining focus on your leadership priorities--no matter how busy you are Three key questions that will help you connect purpose to paycheck for your staff A four-step formula for addressing subpar performance and driving complacency from the workplace A simple coaching model for fast-track staff development Four reward/recognition tools that will leave your employees feeling valued and motivated The one simple activity that will forge deep bonds of trust between you and your employees Three key ingredients that will immediately increase the motivation level of any employee Being a great leader is never easy, but Robbins breaks it all down into essential components to reveal its fundamental simplicity. Nine Minutes on Monday is your road map to igniting purpose, passion, and engagement among your team members. Master and apply the tools and techniques inside, and your employees will be motivated, inspired, and equipped to bring their best to work each and every day. Quick and simple leadership lessons for boosting performance, morale, and engagement "James Robbins is a terrifi c observer, thinker, and storyteller. He also has marvelous insights about how leaders can help employees become more connected to their work setting. He weaves together personal stories with thoughtful leadership insights into a compelling book. If leaders will do the nine minutes he suggests each Monday morning, they will become what we have called 'meaning makers' who deliver enormous value to their employees, customers, investors, and communities."--Dave Ulrich, professor, Ross School of Business, University of Michigan; partner, The RBL Group; coauthor, The Why of Work "It really works! Robbins provides simple and practical tools to help all managers get on the road toward becoming great leaders. These nine easy-to-use principles are relevant to today's work environment and yet so often overlooked. Thank you for helping me to make a difference to my team." -- Sue Travis, HR Manager, Lowe's "Every manager in your workplace needs this book. Practical and easily doable ideas that will help turn your managers into truly inspiring leaders." -- Michael Kerr, "The Workplace Energizer" and author of Putting Humor to Work "Great easy read with lots of practical applications for leaders looking to improve their game and really make a difference in the lives of those they lead." -- Debbie Stein, CFO AltaGas